Career Choice and Self-Efficacy Toward Senior High School Students’ Career Goals in the Philippines - Evelyn T Gimarino (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The study examined the career choices and self-efficacy of Senior High School students in the Philippines and how these are influenced by their demographic profiles such as age, gender, and educational strand. Methodology: The study employed descriptive-correlational study using an adapted questionnaire with sections on demographic profiles, career choices (realistic, investigative, artistic, social, enterprising, and conventional), and self-efficacy (Career Development Self-Efficacy Inventory. Data were collected from 308 Grade 12 students through Google Forms, analyzed using Statistical Package for Social Sciences, and involved ethics review and informed consent. Main Findings: Senior High School strand significantly correlates with career choices and self-efficacy. Age and gender show no significantly impact on career preferences or self-efficacy. Students demonstrate high self-efficacy in career goal-setting and training selection. Novelty/Originality of this study: This study provided new insights into how Senior High School strands influence students’ career choices and self-efficacy, offering targeted recommendations for career guidance programs and advancing understanding of career development in the Philippine educational context.